Severe gastrointestinal haemorrhage from an eroding jejuno-jejunal fistula - Niall Woodley; Stuart O'Toole (Elsevier, 2020)
Children with complex needs often have limited communication which makes clinical assessment extremely difficult. They also require complex feeding regimes and are prone to chronic bowel dysfunction and dysmotility requiring frequent admissions to hospital. We present the case of an 11-year old boy with mosaic trisomy 13 and an end ileostomy (for gut dysmotility) who presented with a catastrophic gastrointestinal haemorrhage during a prolonged Paediatric Intensive Care (PICU) stay recovering from an episode of presumed sepsis. A normal upper GI endoscopy was followed by a laparoscopy which revealed a small bowel adhesion to the anterior abdominal wall which had facilitated the creation of a jejuno-jejunal fistula that had eroded through a mesenteric artery. The child recovered well after a limited laparotomy and segmental small bowel resection.This case highlights an extremely unusual cause of gastrointestinal bleeding in a child and emphasises the role of Laparoscopy in the comprehensive assessment of this presentation. Keywords: Laparoscopy, Gastrointestinal bleeding, Endoscopy